Revealing the Student Philanthropy Movement in the Midst of the COVID-19 Pandemic - Anita Puji Astutik; Safitri Khoirinindyah; Anis Farihah (ISTAWA, 2021)
The philanthropic movement aims to increase student knowledge and involvement in allocating funds to support social activism. At the time of the Covid-19 outbreak, philanthropy-based da'wah was a common form of da'wah carried out by students with the Muhammadiyah Covid-19 command center. This means that students and the Muhammadiyah Covid-19 Command Center "MCCC" were involved in dealing with the Covid-19 epidemic and have continued to do so. Using qualitative research, this study was conducted in 2020-2021 with the goal of describing and narrating the student philanthropy movement in the midst of the covid-19 pandemic. The data gathering method was "triangulation," which included observation, interviews, literature review, and documentation. Researchers used the approach of "persistent observation" to apply the data analysis process. The philanthropic movement seeks Muhammadiyah students' participation in propagating diverse da'wah material based on the philanthropic movement, which encompasses advocacy, donating, and service. During the extensive covid-19 pandemic, the surrounding community can learn about the charitable activity carried out by students in partnership with the Muhammadiyah Covid-19 Command Center. As a result, a network is developed to raise public awareness about COVID-19 and to assist in its management through the Philanthropy Movement. As a result, the Muhammadiyah student volunteers' movement in partnership with the Muhammadiyah Covid-19 Command Center is extremely forward-thinking. Social activities for Muhammadiyah students are easier in current times, therefore fundraising for areas affected by COVID-19 is quite advanced, and helping the community deal with calamities and individuals in need is very simple